Addition of the microchromosome GGA25 to the chicken genome sequence assembly through radiation hybrid and genetic mapping - Douaud, Marine (BioMed Central, 2008)
BACKGROUND: The publication of the first draft chicken sequence assembly became available in 2004 and was updated in 2006. However, this does not constitute a definitive and complete sequence of the chicken genome, since the microchromosomes are notably under-represented. In an effort to develop maps for the microchromosomes absent from the chicken genome assembly, we developed radiation hybrid (RH) and genetic maps with markers isolated from sequence currently assigned to "chromosome Unknown" (chrUn). The chrUn is composed of sequence contigs not assigned to named chromosomes. To identify and map sequence belonging to the microchromosomes we used a comparative mapping strategy, and we focused on the small linkage group E26C13. RESULTS: In total, 139 markers were analysed with the chickRH6 panel, of which 120 were effectively assigned to the E26C13 linkage group, the remainder mapping elsewhere in the genome. The final RH map is composed of 22 framework markers extending over a 245.6 cR distance. A corresponding genetic map was developed, whose length is 103 cM in the East Lansing reference population. The E26C13 group was assigned to GGA25 (Gallus gallus chromosome 25) by FISH (fluorescence in situ hybridisation) mapping. CONCLUSION: The high-resolution RH framework map obtained here covers the entire chicken chromosome 25 and reveals the existence of a high number of intrachromosomal rearrangements when compared to the human genome. The strategy used here for the characterization of GGA25 could be used to improve knowledge on the other uncharacterized small, yet gene-rich microchromosomes.